210Po in Human Saliva of Smokeless Tobacco Users. Issue 1 (January 2017) - Meli, Maria Assunta; Desideri, Donatella; Roselli, Carla; Feduzi, Laura
Abstract : Abstract: The occurrence and mobility of 210 Po in oral smokeless tobacco products (STPs) were determined because its effects on human health must be taken into account. This research was subdivided into two parts: determination by alpha spectrometry of the 210 Po activity concentration in 16 oral smokeless tobacco products of different brands purchased in local specialty stores in Europe and evaluation of its percent extraction into an artificial salivary gland during sucking or chewing operations. Polonium-210 was detected in all samples, and its concentrations ranged from 3.46 to 14.8 Bq kg −1 (mean value of 7.45 ± 3.82 Bq kg −1 ). The highest concentration was found in chewing tobacco. The samples showed no significant difference in the content of 210 Po level. The data obtained in this study show that the polonium, although poorly extracted (12.8 ± 8.96%) by artificial saliva, is not totally retained within the smokeless tobacco products, with a consequent potential health hazard associated with oral use of these products.